Generation of vertical angular momentum in single, double, and triple-turn pirouette en dehors in ballet - Kim, J.; Wilson, M. A.; Singhal, K.; Gamblin, S.; Suh, S. Y.; Kwon, Y. H. (Sports Biomechanics, 2014)
The purpose of this study was to investigate the vertical angular momentum generation strategies used by skilled ballet dancers in pirouette en dehors. Select kinematic parameters of the pirouette preparation (stance depth, vertical center-of-mass motion range, initial shoulder line position, shoulder line angular displacement, and maximum trunk twist angle) along with vertical angular momentum parameters during the turn (maximum momentums of the whole body and body parts, and duration and rate of generation) were obtained from nine skilled collegiate ballet dancers through a three-dimensional motion analysis and compared among three turn conditions (single, double, and triple). A one-way (`turn`) multivariate analysis of variance of the kinematic parameters and angular momentum parameters of the whole body and a two-way analysis of variance (`turn` £ `body`) of the maximum angular momentums of the body parts were conducted. Significant `turn` effects were observed in the kinematic/angular momentum parameters (both the preparation and the turn) (p , 0.05). As the number of turns increased, skilled dancers generated larger vertical angular momentums by predominantly increasing the rate of momentum generation using rotation of the upper trunk and arms. The trail (closing) arm showed the largest contribution to whole-body angular momentum followed by the lead arm.